2016
DOI: 10.3847/0004-637x/823/1/34
|View full text |Cite
|
Sign up to set email alerts
|

The Inclination Angle and Evolution of the Braking Index of Pulsars With Plasma-Filled Magnetosphere: Application to the High Braking Index of PSR J1640–4631

Abstract: The recently discovered rotationally powered pulsar PSR J1640-4631 is the first to have a braking index measured, with high enough precision, that is greater than three. An inclined magnetic rotator in vacuum or plasma would be subject not only to spin-down but also to an alignment torque. The vacuum model can address the braking index only for an almost orthogonal rotator that is incompatible with the single peaked pulse profile. The magnetic dipole model with the corotating plasma predicts braking indices be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…Indeed, the plasma filled magnetosphere evolution of the inclination angle offers another interpretation of a braking index larger than 3 (Ekşi et al 2016). In the same vain, Philippov, Tchekhovskoy & Li (2014) accounted for plasma filled magnetospheres in the force-free and MHD limit contributing to the total torque and therefore to the subsequent obliquity evolution.…”
Section: J Pétrimentioning
confidence: 99%
“…Indeed, the plasma filled magnetosphere evolution of the inclination angle offers another interpretation of a braking index larger than 3 (Ekşi et al 2016). In the same vain, Philippov, Tchekhovskoy & Li (2014) accounted for plasma filled magnetospheres in the force-free and MHD limit contributing to the total torque and therefore to the subsequent obliquity evolution.…”
Section: J Pétrimentioning
confidence: 99%
“…All these braking indices are remarkably smaller than the canonical value (n = 3), which is expected for pure magneto-dipole radiation model (see, e.g., Lyne et al 1993Lyne et al , 1996Livingstone et al 2007;Espinoza et al 2011;Weltevrede et al 2011;Roy et al 2012;Archibald et al 2015). Several interpretations for the observed braking indices have been put forward, like the ones that propose either accretion of fall-back material via a circumstellar disk (Chen & Li 2016), the so-called quantum vacuum friction (QVF) effect , relativistic particle winds (Xu & Qiao 2001;Wu et al 2003) to explain the observed braking index ranges (see e.g., Allen & Horvath 1997;Ekşi et al 2016, and references therein for further models). Another possibility is that the magnetic moment of the star changes in time, through either a change in the surface field strength or the angle between the magnetic and spin axes (see, e.g., Muslimov & Page 1995;Pandey & Prasad 1996;Link et al 1998;Epstein & Link 2000, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Several interpretations for the observed braking indices have been put forward, like the ones that propose either accretion of fall-back material via a circumstellar disk [10], relativistic particle winds [11,12], or modified canonical models to explain the observed braking index ranges (see e.g., [13][14][15], and references therein for further models). Alternatively, it has been proposed that the so-called quantum vacuum friction (QVF) effect in pulsars can explain several aspects of their phenomenology [16].…”
Section: Introductionmentioning
confidence: 99%